2021
DOI: 10.1002/jbio.202170015
|View full text |Cite
|
Sign up to set email alerts
|

Front Cover

Abstract: The possibilities of using Mueller matrix (MM) imaging polarimetry to assess meat quality have not yet been sufficiently explored. In the current study, the fresh porcine muscles are imaged at room emperature with a wide‐field MM imaging polarimeter over 26 hours to visualize dynamics of tissue optical properties through applying Lu‐Chipman decomposition. The MM images, frequency distribution histograms and statistical analysis of the MM elements show prominent changes over time. Further details can be found i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
1
Order By: Relevance
“…These are the most remarkable changes we observed during the meat degradation process. However, it is worth noting that this particular behavior has not been documented in previous studies and seems to contradict the findings reported in [31], where an increase in retardation values over time was attributed to muscle fiber densification resulting from water loss.…”
Section: Degradation Of Fresh Meatcontrasting
confidence: 84%
See 1 more Smart Citation
“…These are the most remarkable changes we observed during the meat degradation process. However, it is worth noting that this particular behavior has not been documented in previous studies and seems to contradict the findings reported in [31], where an increase in retardation values over time was attributed to muscle fiber densification resulting from water loss.…”
Section: Degradation Of Fresh Meatcontrasting
confidence: 84%
“…Numerous previous studies [11,31,32] have investigated the changes in polarization-based properties of raw meat over time, highlighting the potential of Mueller matrix imaging in assessing meat freshness. Consistent with these findings, our research has revealed significant alterations in the polarimetric characteristics of meat tissues, most particularly in skeletal muscle.…”
Section: Degradation Of Fresh Meatmentioning
confidence: 99%
“…Although integrated QWPs have been demonstrated [4] to produce or detect free-space CPL, to the best of our knowledge, there are no PICs routing CPL through optical chips. However, CPL is the relevant polarization for many applications, to name a few, 3D displays, antiglare screens, biomedical diagnosis and imaging, [5,6] drug control and development, [7] food control, [8] spin-orbit coupling, [9] valleytronic, etc. [10,11] The simplest idea to allow CPL propagation in PICs without loss of polarization is to suppress the linear birefringence LB with zero-birefringence (ZBR) waveguides.…”
Section: Introductionmentioning
confidence: 99%
“…Revealing the mechanisms of interaction between photons and complex biological tissues is one of the major goals of biomedical optics research, which is essential for therapeutic and diagnostic applications [1–9]. Polarization is one of the fundamental properties of light and a promising method that has been applied to many fields, including biological tissues [3, 10–14]. Most biological tissues are structurally anisotropic turbid media containing fibrous components, such as axons, capillary vessels, collagen fibers or myofibrils [15].…”
Section: Introductionmentioning
confidence: 99%